Penerapan Kombinasi Genetic Algorithm dan Iterated Local Search Pada Multi-Depot Capacitated Vehicle Routing Problem - Safira, Inggrid Dwi (Jurnal Matematika; Vol 11 No 1 (2021), 2021)
The distribution is a system for distributing goods or products from the company to customers. Multi-depot capacitated vehicle routing problem (MDCVRP) is a variation of the vehicle routing problem (VRP) which is based on distribution problems and MDCVRP is a topic of optimization problems in applied mathematics. In this study, the authors apply a combination of two metaheuristic algorithms, namely the G enetic A lgorithm (GA) and I terated L ocal S earch (ILS), hereinafter referred to as the GA&ILS algorithm. This study aims to analyze the effectiveness and efficiency of the application of the GA&ILS algorithm to solve MDCVRP on 20 simulation data grouped into four sizes (25, 50, 75, and 100 customer points) . Based on the results of the research, it was found that the GA&ILS algorithm is quite effective for small-scale data, but less effective for large-scale data. From the results of the analysis carried out, the GA&ILS algorithm still has drawbacks, it is less able to avoid being trapped by the local optimum. In addition, the GA&ILS algorithm requires a long computational time, making it less efficient.